West of wicked - St. Crowe, Nikki (St. Crowe, Nikki. Great and terrible land, 2026)
"Dorothy Gale doesn't know where she came from. At the age of five, she was dropped on Em and Henry's doorstep while a terrible storm rolled across the Kansas prairie. Now as an adult, Dorothy has made the most of her life on the farm. But when a cyclone tears through the night, ripping her, her dog, and the farmhouse away, Dorothy wakes to find herself far from home in the strange, cursed land of Oz. Desperate to find her way back, Dorothy takes the advice of the Witch of the North and sets off on the yellow brick road to find a wizard...with a warning to avoid forest monsters, heartless mercenaries, and wicked witches. It isn't long before Dorothy encounters the dark side of Oz, stumbling on a man beaten and bloody, tied to a pole in a cornfield. Not unlike the scarecrows on the Kansas farm. With no memories, the mysterious stranger joins Dorothy. Rook is ridiculously handsome, endlessly charming, and somehow understands Dorothy in a way no one ever has. But when they cross paths with the infamous Tinman and his axe, Rook proves he may be hiding his own secrets. Nothing and no one is what they seem in the cursed land of Oz...maybe even Dorothy herself"-- Provided by publisher.